Tuberculosis incidence in patients with psoriasis who receive anti- TNF- alpha therapies in Latin America: systematic review and meta-analysis - Contreras Maza, Roniel Gonzalo (2019)
The global incidence of tuberculosis in patients with psoriasis who receive anti- tumoral necrosis factor (TNF)- alpha in Latin America remains unknown, despite of the increasing use of those therapies and the local high incidences of tuberculosis, so a systematic review and meta-analysis on the subject was carried out. For that review, there were included studies reporting the tuberculosis incidence in patients with psoriasis receiving anti- TNF- alpha in Latin America, using four electronical databases: Pubmed, Scielo, LILACS and Medigraphic, and then to perform a meta-analysis about those incidences in order to obtain pooled proportions. Finally, 9 studies were selected, which were performed in Argentina, Brasil, Chile, Colombia and México, with a total follow-up of 510,9 patient-years, and with three cases of tuberculosis, giving a pooled incidence of 636 cases of tuberculosis per 100,000 patient-years (95% confidence interval [CI 95%]: 145-1764 per 100,000 patient-years), after using the fixed effects model, which was high according to the stimates of the regional population- based tuberculosis incidence, and similar to other studies performed in patients with psoriasis who receive anti- TNF- alpha in different locations.